BIM Adoption for effective interface management in Indian construction industries - Sindhu Vaardini Umaapathy; Shanmugapriya Sundarrajan (Građevinar)
The contribution of the construction industry towards the development of the economy of an economy is inevitable. Building Information Modelling (BIM) is an emerging information tool that supports interface management in construction projects based on intellectual digital illustration that provides a maximum number of benefits throughout the lifecycle of projects. A country like India has recently adopted the BIM tool, but it is not widely adopted by construction companies. Therefore, comprehensive and systematic analyses are essential for determining the factors influencing BIM adoption. In this study, a proposed model is employed using seven significant factors, namely, Organizational support (OS), Information Quality (IQ), System Quality (SQ), Service Quality (SRQ), usage (U), User Satisfaction (US), and Net Benefits (NB), to analyse the influence of these factors on BIM adoption. An experimental analysis was conducted based on the developed success model and the fitness of the model was estimated. The results of this model suggest that system quality plays a major role in BIM usage. Furthermore, a hypothesis test was performed to analyse the impact range of each independent factor over the dependent factors.